Falling upwards how we took to the air - Holmes, Richard 1945- (William Collins, 2013)
Falling Upwards tells the story of the enigmatic group of men and women who first risked their lives to take to the air, and so discovered a new dimension of human experience. Why they did it, what their contemporaries thought of them, and how their flights revealed the secrets of our planet in wholly unexpected ways is its subject.